Effects of heat treatment on microstructure and mechanical properties of TiC/TiB composite bioinert ceramic coatings in-situ synthesized by laser cladding on Ti6Al4V. Issue 1 (1st January 2021) - Chen, Tao; Li, Wenpeng; Liu, Defu; Xiong, Yi; Zhu, Xiangcheng
Abstract: To improve the wear resistance of titanium alloy, in this work, TiC/TiB composite bioinert ceramic coatings were synthesized in-situ via laser cladding using Ti and B4 C mixed powders as precursor materials. And to decrease the impact of the excessive residual tensile stress generated by the uneven temperature distribution on the performance of coatings, the coatings were then subsequently heated for 3 h at different temperatures (400 °C, 600 °C, and 800 °C) and then air cooled. The effects of heat treatment on the microstructure, residual stress, micro-hardness, fracture toughness, and wear resistance of the coatings were investigated. The results showed that phase compositions and microstructure of the heat-treated coatings were virtually identical to that of the untreated coatings; however, the precipitation of acicular TiB enhanced mechanical properties of the heat-treated coatings. In addition, the average residual tensile stress values of the coatings decreased as the heat treatment temperature increased, which improved fracture toughness of the coatings from 3.95 to 4.68 MPa m 1/2 . Moreover, wear resistance of the coatings was greatly enhanced by heat treatment; as the wear volume of the heat-treated coatings decreased by 50% at 800 °C compared with that of the untreated coatings. Lastly, the coatings showed good biocompatibility after being evaluated in vitro, and therefore had broad application prospects in the field of orthopedic implants.